Cash holdings and corporate performance: Evidence from Sri Lanka - Vijayakumaran, R.; Atchyuthan, N. (International Journal of Accounting & Business Finance, 2017)
Recently, debate on corporate cash holdings has received greater attention in the corporate finance literature. Corporate finance theories provide competing hypotheses on the relationship between cash holdings and corporate performance. This study empirically examines the relationship between cash holdings and corporate performance using a sample of firms listed in the Colombo Stock Exchange (CSE) over the period 2011-2115. Controlling for unobserved heterogeneity and other firm characteristics, this study finds that cash holdings is positively related to firm performance.
Keywords: Cash Holdings; Corporate Performance; Agency Conflicts